Формирование поликультурной образовательной среды как средства интенсификации обучения русскому языку как иностранному - Кипнес, Людмила; Непоклонова, Елена (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The article discusses ways of forming a multicultural educational environment as an actual means of effective teaching of Russian as a foreign language. Methodological issues are considered in close interaction with the issues of the relationship between science and culture at the present stage, special attention is paid to the decisive role of methodological reflection in the competence model of a modern researcher and how to form it in the process of teaching research skills at the stages of school and university learning using the example of teaching the Russian language as to foreign. Particular attention is paid to modern educational projects aimed at creating an effective multicultural interaction between students studying Russian as a foreign language in order to intensify learning. In the framework of the multicultural interaction project between Turkmen and Russian students, implemented at the Russian State Medical University, the article discusses the methodological aspects of linguistic Olympiads and the joint project activities of Turkmen and Russian students. The article also discusses the prospects of creating a Russian-Turkmen language center on the basis of the university as a scientific community of teachers and students, suggesting a flexible system of various types and methods of integration in order to solve various professional problems.
Keywords: методологическая рефлексия; поликультурная среда; сетевое сообщество; проектная деятельность; олимпиада; задача; methodological reflection; multicultural environment; network community; project activity; olympiad; task